Processing technology of magnesia carbon brick with high corrosion resistance
By using specific proportions and treatment methods of materials such as magnesium sand particles in the preparation process of magnesium carbon bricks, the problem of insufficient corrosion resistance of magnesium carbon bricks in high temperature and high corrosion environments is solved, and more efficient detection and more stable Performance performance.
Patent Information
- Application Number
- CN202411073049.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2024-12-13
AI Technical Summary
The existing magnesium carbon brick preparation process has insufficient corrosion resistance in high temperature and high corrosion environments, resulting in poor use in harsh environments.
Magnesium sand particles, magnesium sand powder, alloy magnesium, graphite, coke, silicon carbide, phenolic resin and antioxidants are used to match in a specific proportion. After mixing, injection molding and sintering, combined with palletizing and cooling treatment, the corrosion resistance is finally carried out. Test.
It improves the corrosion resistance and detection efficiency of magnesium carbon bricks, can classify and inspect the finished products, extends the service life of magnesium carbon bricks and enhances its reliability in harsh environments.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesia carbon brick preparation, in particular to a processing technology of magnesia carbon bricks with high corrosion resistance. Background Art
[0002] Magnesia carbon bricks are non-burning carbon composite refractory materials made of high melting point basic oxide magnesium oxide (melting point 2800℃) and high melting point carbon material that is difficult to be wetted by slag as raw materials, adding various non-oxide additives and combining them with carbonaceous binders.
[0003] The preparation process of magnesia carbon bricks on the market, when preparing magnesia carbon bricks, mostly uses simple components such as magnesium powder, magnesium particles, graphite, etc., which leads to the problem of relatively poor corrosion performance after molding. The use environment of magnesia carbon bricks is relatively harsh, generally a high temperature and highly corrosive environment, and the corrosion resistance is not ideal, which will lead to magnesia carbon bricks with poor resistance and unable to adapt to relatively harsh environments. The demand for the use of magnesia carbon bricks is poor. For this reason, we propose a high corrosion resistance magnesia carbon brick processing technology. Summary of the invention
[0004] The object of the present invention is to provide a process for processing magnesia carbon bricks with high corrosion resistance to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a high corrosion-resistant magnesia-carbon brick processing technology, the manufacturing process of the high corrosion-resistant magnesia-carbon brick processing technology has the following steps:
[0006] (1) Proportioning raw materials: magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant are mixed in proportion;
[0007] (2) Mixing raw materials: mixing magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant in a certain proportion to prepare raw materials;
[0008] (3) Molding preparation: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to complete the material preparation;
[0009] (4) Sintering: Place the prepared mold in a kiln for sintering;
[0010] (5) Stacking treatment: Remove the magnesia carbon brick products sintered in the kiln, stack them, and let them stand for 8-30 hours to cool down;
[0011] (6) Final test: The finished magnesia carbon bricks are tested for corrosion resistance;
[0012] Preferably, the raw materials are mixed in the following proportions: 20-30 parts of magnesia particles, 10-20 parts of magnesia powder, 5-15 parts of alloy magnesium, 10-15 parts of graphite, 15-20 parts of coke, 5-10 parts of silicon carbide, 3-5 parts of phenolic resin, and 2-6 parts of antioxidant.
[0013] Preferably, the magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin and antioxidant are mixed and stirred for 20-40 minutes in a mixer at 100-200 revolutions per minute.
[0014] Preferably, the molding preparation is as follows: the mold is first preheated to 150-300° C., and then the mixed raw materials are injected into the magnesium carbon brick mold by an injection machine, and the mold is vibrated to compact the raw materials in the mold to complete the preparation.
[0015] Preferably, the sintering molding: the prepared mold is placed in a kiln for sintering molding. During sintering, the kiln is first preheated to 500°C, and then the prepared mold is placed in the kiln for sintering for 1-4 hours. During the sintering process, the temperature is gradually increased and finally increased to 1700-1900°C. After sintering, the mold is taken out and then left to cool for 20-80 minutes.
[0016] Preferably, the stacking treatment is as follows: the magnesia carbon brick products sintered in the kiln are removed, stacked into stacks of 3-5 meters in length, 2-4 meters in width and 2-3 meters in height, and then cooled by blowing with a M3 fan per minute for 3-5 hours.
[0017] Preferably, the finished magnesia carbon bricks are subjected to corrosion resistance testing:
[0018] (2) Corrosion resistance test: The finished magnesia carbon bricks are placed in a chemical pool for testing. The chemical pool is a rectangular pool with a length of 4-6 meters, a width of 3-5 meters, and a depth of 2-3 meters. A solution of 80% water and 20% sodium chloride is poured into the pool. The finished magnesia carbon brick test samples are classified into three categories and placed in the pool water respectively. The first category is kept still for 3-5 hours, the second category is kept still for 8-15 hours, and the third category is kept still for 40-60 hours to test the corrosion resistance of the magnesia carbon bricks.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The processing technology of the highly corrosion-resistant magnesium carbon brick has a poor detection efficiency, and the magnesium carbon bricks cannot be tested in batches. During the detection, only a single sample can be simply tested, and the samples cannot be divided into batches for centralized detection. In this chemical pool, a large number of magnesium carbon brick detection samples can be stored in a centralized manner, and the samples can be classified for detection, divided into time, and different types of samples can be tested at different times to detect the strength of the corrosion resistance of magnesium carbon bricks;
[0021] 2. The highly corrosion-resistant magnesia carbon brick processing technology stacks and cools the magnesia carbon bricks, making them cool more efficiently. At the same time, the stacked magnesia carbon bricks are slowly cooled, making the performance of the magnesia carbon bricks more stable after cooling, making them safer and more reliable when used. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] The present invention provides a technical solution: a high corrosion-resistant magnesia-carbon brick processing technology, the manufacturing process of the high corrosion-resistant magnesia-carbon brick processing technology has the following steps:
[0024] (1) Proportioning raw materials: magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant are mixed in proportion;
[0025] (2) Mixing raw materials: mixing magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant in a certain proportion to prepare raw materials;
[0026] (3) Molding preparation: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to complete the material preparation;
[0027] (4) Sintering: Place the prepared mold in a kiln for sintering;
[0028] (5) Stacking treatment: Remove the magnesia carbon brick products sintered in the kiln, stack them, and let them stand for 8-30 hours to cool down;
[0029] (6) Final test: The finished magnesia carbon bricks are tested for corrosion resistance;
[0030] Preferably, the raw materials are mixed in the following proportions: 20-30 parts of magnesia particles, 10-20 parts of magnesia powder, 5-15 parts of alloy magnesium, 10-15 parts of graphite, 15-20 parts of coke, 5-10 parts of silicon carbide, 3-5 parts of phenolic resin, and 2-6 parts of antioxidant.
[0031] Preferably, the magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin and antioxidant are mixed and stirred for 20-40 minutes in a mixer at 100-200 revolutions per minute.
[0032] Preferably, the molding preparation is as follows: the mold is first preheated to 150-300° C., and then the mixed raw materials are injected into the magnesium carbon brick mold by an injection machine, and the mold is vibrated to compact the raw materials in the mold to complete the preparation.
[0033] Preferably, the sintering molding: the prepared mold is placed in a kiln for sintering molding. During sintering, the kiln is first preheated to 500°C, and then the prepared mold is placed in the kiln for sintering for 1-4 hours. During the sintering process, the temperature is gradually increased and finally increased to 1700-1900°C. After sintering, the mold is taken out and then left to cool for 20-80 minutes.
[0034] Preferably, the stacking treatment is as follows: the magnesia carbon brick products sintered in the kiln are removed, stacked into stacks of 3-5 meters in length, 2-4 meters in width and 2-3 meters in height, and then cooled by blowing with a M3 fan per minute for 3-5 hours.
[0035] Preferably, the finished magnesia carbon bricks are subjected to corrosion resistance testing:
[0036] (2) Corrosion resistance test: The finished MgO-C bricks are placed in a chemical pool for testing. The chemical pool is a rectangular pool with a length of 4-6 meters, a width of 3-5 meters, and a depth of 2-3 meters. A solution of 80% water and 20% sodium chloride is poured into the pool. The finished MgO-C brick test samples are classified into three categories and placed in the pool water respectively. The first category is kept still for 3-5 hours, the second category is kept still for 8-15 hours, and the third category is kept still for 40-60 hours to test the corrosion resistance of the MgO-C bricks.
[0037] Example 2:
[0038] A high corrosion-resistant magnesia carbon brick processing technology, the manufacturing process of the high corrosion-resistant magnesia carbon brick processing technology has the following steps:
[0039] (1) Proportioning raw materials: magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant are mixed in proportion;
[0040] (2) Mixing raw materials: mixing magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant in a certain proportion to prepare raw materials;
[0041] (3) Molding preparation: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to complete the material preparation;
[0042] (4) Sintering: Place the prepared mold in a kiln for sintering;
[0043] (5) Stacking treatment: Remove the magnesia carbon brick products sintered in the kiln, stack them, and let them stand for 8-20 hours to cool down;
[0044] (6) Final test: The finished magnesia carbon bricks are tested for corrosion resistance;
[0045] Preferably, the raw materials are mixed in the following proportions: 25-30 parts of magnesia particles, 15-20 parts of magnesia powder, 10-15 parts of alloy magnesium, 10-13 parts of graphite, 15-18 parts of coke, 5-8 parts of silicon carbide, 4-5 parts of phenolic resin, and 3-6 parts of antioxidant.
[0046] Preferably, the magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin and antioxidant are mixed and stirred for 30-40 minutes at 150-200 revolutions per minute using a mixer.
[0047] Preferably, the molding preparation is as follows: the mold is first preheated to 200-300° C., and then the mixed raw materials are injected into the magnesium carbon brick mold by an injection machine, and the mold is vibrated to compact the raw materials in the mold to complete the preparation.
[0048] Preferably, the sintering molding: the prepared mold is placed in a kiln for sintering molding. During sintering, the kiln is first preheated to 500°C, and then the prepared mold is placed in the kiln for sintering for 2-4 hours. During the sintering process, the temperature is gradually increased and finally increased to 1800-1900°C. After sintering, the mold is taken out and then left to cool for 30-80 minutes.
[0049] Preferably, the stacking treatment is as follows: the magnesia carbon brick products sintered in the kiln are removed, stacked into stacks of 4-5 meters in length, 3-4 meters in width and 2-3 meters in height, and then cooled by blowing with a M3 fan per minute for 3-4 hours.
[0050] Preferably, the finished magnesia carbon bricks are subjected to corrosion resistance testing:
[0051] (2) Corrosion resistance test: The finished MgO-C bricks are placed in a chemical pool for testing. The chemical pool is a rectangular pool with a length of 5-6 meters, a width of 4-5 meters, and a depth of 2-2.5 meters. A solution of 80% water and 20% sodium chloride is poured into the pool. The finished MgO-C brick test samples are classified into three categories and placed in the pool water respectively. The first category is kept still for 3-4 hours, the second category is kept still for 8-10 hours, and the third category is kept still for 40-50 hours to test the corrosion resistance of the MgO-C bricks.
[0052] Example 3:
[0053] A high corrosion-resistant magnesia carbon brick processing technology, the manufacturing process of the high corrosion-resistant magnesia carbon brick processing technology has the following steps:
[0054] (1) Proportioning raw materials: magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant are mixed in proportion;
[0055] (2) Mixing raw materials: mixing magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant in a certain proportion to prepare raw materials;
[0056] (3) Molding preparation: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to complete the material preparation;
[0057] (4) Sintering: Place the prepared mold in a kiln for sintering;
[0058] (5) Stacking treatment: Remove the magnesia carbon brick products sintered in the kiln, stack them, and let them stand for 8-20 hours to cool down;
[0059] (6) Final test: The finished magnesia carbon bricks are tested for corrosion resistance;
[0060] Preferably, the raw materials are mixed in the following proportions: 28-30 parts of magnesia particles, 17-20 parts of magnesia powder, 12-15 parts of alloy magnesium, 12-13 parts of graphite, 16-18 parts of coke, 7-8 parts of silicon carbide, 4-4.5 parts of phenolic resin, and 3-5 parts of antioxidant.
[0061] Preferably, the magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin and antioxidant are mixed and stirred for 30-35 minutes at 160-200 revolutions per minute using a mixer.
[0062] Preferably, the molding preparation is as follows: the mold is first preheated to 250-300° C., and then the mixed raw materials are injected into the magnesium carbon brick mold by an injection machine, and the mold is vibrated to compact the raw materials in the mold to complete the preparation.
[0063] Preferably, the sintering molding: the prepared mold is placed in a kiln for sintering molding. During sintering, the kiln is first preheated to 500°C, and then the prepared mold is placed in the kiln for sintering for 3-4 hours. During the sintering process, the temperature is gradually increased and finally increased to 1800-1850°C. After sintering, the mold is taken out and then cooled down for 30-60 minutes.
[0064] Preferably, the stacking treatment is as follows: the magnesia carbon brick products sintered in the kiln are removed, stacked into stacks of 4-4.5 meters in length, 3-3.5 meters in width and 2 meters in height, and then cooled by blowing with a M3 per minute fan for 3-3.5 hours.
[0065] Preferably, the finished magnesia carbon bricks are subjected to corrosion resistance testing:
[0066] (2) Corrosion resistance test: The finished MgO-C bricks are placed in a chemical pool for testing. The chemical pool is a rectangular pool with a length of 5-6 meters, a width of 4-5 meters, and a depth of 2-2.5 meters. A solution of 80% water and 20% sodium chloride is poured into the pool. The finished MgO-C brick test samples are classified into three categories and placed in the pool water respectively. The first category is kept still for 3-4 hours, the second category is kept still for 8-9 hours, and the third category is kept still for 40-45 hours to test the corrosion resistance of the MgO-C bricks.
[0067] Example 4:
[0068] A high corrosion-resistant magnesia carbon brick processing technology, the manufacturing process of the high corrosion-resistant magnesia carbon brick processing technology has the following steps:
[0069] (1) Proportioning raw materials: magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant are mixed in proportion;
[0070] (2) Mixing raw materials: mixing magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant in a certain proportion to prepare raw materials;
[0071] (3) Molding preparation: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to complete the material preparation;
[0072] (4) Sintering: Place the prepared mold in a kiln for sintering;
[0073] (5) Stacking treatment: Remove the magnesia carbon brick products sintered in the kiln, stack them, and let them stand for 8-20 hours to cool down;
[0074] (6) Final test: The finished magnesia carbon bricks are tested for corrosion resistance;
[0075] Preferably, the raw materials are mixed in the following proportions: 30 parts of magnesia particles, 18 parts of magnesia powder, 14 parts of alloy magnesium, 12 parts of graphite, 16 parts of coke, 8 parts of silicon carbide, 4 parts of phenolic resin, and 4 parts of antioxidant.
[0076] Preferably, the magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin and antioxidant are mixed and stirred for 35 minutes using a mixer at 180 revolutions per minute.
[0077] Preferably, the molding preparation is as follows: the mold is first preheated to 300° C., and then the mixed raw materials are injected into the magnesium carbon brick mold by an injection machine, and the mold is vibrated to compact the raw materials in the mold to complete the preparation.
[0078] Preferably, the sintering molding: the prepared mold is placed in a kiln for sintering molding. During sintering, the kiln is first preheated to 500°C, and then the prepared mold is placed in the kiln and sintered for 3 hours. During the sintering process, the temperature is gradually increased and finally increased to 1850°C. After sintering, the mold is taken out and then left to cool for 50 minutes.
[0079] Preferably, the stacking process is as follows: the magnesia carbon brick products sintered in the kiln are removed, stacked into stacks of 4 meters in length, 3 meters in width and 2 meters in height, and then cooled by blowing with a M3 per minute fan for 3 hours.
[0080] Preferably, the finished magnesia carbon bricks are subjected to corrosion resistance testing:
[0081] (2) Corrosion resistance test: The finished magnesia carbon bricks are placed in a chemical pool for testing. The chemical pool is a rectangular pool with a length of 6 meters, a width of 4 meters, and a depth of 2 meters. A solution of 80% water and 20% sodium chloride is poured into the pool. The finished magnesia carbon brick test samples are classified into three categories and placed in the pool water respectively. The first category is kept still for 3 hours, the second category is kept still for 8 hours, and the third category is kept still for 45 hours to test the corrosion resistance of the magnesia carbon bricks.
[0082] Working principle: For this type of high corrosion-resistant magnesium carbon brick processing technology, the detection efficiency is poor, and the magnesium carbon bricks cannot be tested in batches. During the detection, only a single sample can be simply tested, and the samples cannot be divided into batches for centralized detection. In this chemical pool, a large number of magnesium carbon brick detection samples can be stored in a centralized manner, and the samples can be classified for detection. Different types of samples can be tested at different times to detect the strength of the corrosion resistance of the magnesium carbon bricks. The magnesium carbon bricks are stacked and cooled to make the magnesium carbon bricks cool more efficiently. At the same time, the stacked magnesium carbon bricks are slowly cooled, so that after the magnesium carbon bricks are cooled, their performance is more stable, safer to use, and more reliable. In this way, the entire use process of the high corrosion-resistant magnesium carbon brick processing technology is completed.
[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is limited by the appended claims and their equivalents.
Claims
1. A high corrosion resistance magnesia carbon brick processing technology, It is characterized in that The manufacturing process of the highly corrosion-resistant magnesia-carbon brick processing technology has the following steps: (1) Proportioning raw materials: magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant are mixed in proportion; (2) Mixing raw materials: mixing magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin, and antioxidant in a certain proportion to prepare raw materials; (3) Molding preparation: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to complete the material preparation; (4) Sintering: Place the prepared mold in a kiln for sintering; (5) Stacking treatment: Remove the magnesia carbon brick products sintered in the kiln, stack them, and let them stand for 8-30 hours to cool down; (6) Final test: The finished magnesia carbon bricks are tested for corrosion resistance.
2. A process for processing highly corrosion-resistant magnesia-carbon bricks according to claim 1, Features: The raw materials are mixed in the following proportions: 20-30 parts of magnesia particles, 10-20 parts of magnesia powder, 5-15 parts of alloy magnesium, 10-15 parts of graphite, 15-20 parts of coke, 5-10 parts of silicon carbide, 3-5 parts of phenolic resin and 2-6 parts of antioxidant.
3. A process for processing highly corrosion-resistant magnesia-carbon bricks according to claim 1, Features: The magnesia particles, magnesia powder, magnesium alloy, graphite, coke, silicon carbide, phenolic resin and antioxidant are mixed and stirred for 20-40 minutes in a mixer at 100-200 revolutions per minute.
4. A process for processing highly corrosion-resistant magnesia-carbon bricks according to claim 1, Features: The molding preparation is as follows: the mold is preheated to 150-300° C., and then the mixed raw materials are injected into the magnesium carbon brick mold by an injection machine. The mold is vibrated to compact the raw materials in the mold, and the preparation is completed.
5. A process for processing highly corrosion-resistant magnesia-carbon bricks according to claim 1, Features: The sintering molding: placing the prepared mold in a kiln for sintering molding. During sintering, first preheat the kiln to 500° C., then place the prepared mold in the kiln, and sinter for 1-4 hours. During the sintering process, the temperature is gradually increased, and finally the temperature is increased to 1700-1900° C. After sintering, take out the mold and then keep it still for 20-80 minutes to cool down.
6. A process for processing highly corrosion-resistant magnesia-carbon bricks according to claim 1, Features: The stacking process is as follows: the magnesia carbon brick products sintered in the kiln are removed, stacked into stacks of 3-5 meters in length, 2-4 meters in width and 2-3 meters in height, and then cooled by blowing with a M3 fan per minute for 3-5 hours.
7. A process for processing highly corrosion-resistant magnesia-carbon bricks according to claim 1, Features: The finished magnesia carbon bricks are subjected to corrosion resistance testing: (2) Corrosion resistance test: The finished magnesia carbon bricks are placed in a chemical pool for testing. The chemical pool is a rectangular pool with a length of 4-6 meters, a width of 3-5 meters, and a depth of 2-3 meters. A solution of 80% water and 20% sodium chloride is poured into the pool. The finished magnesia carbon brick test samples are classified into three categories and placed in the pool water respectively. The first category is kept still for 3-5 hours, the second category is kept still for 8-15 hours, and the third category is kept still for 40-60 hours to test the corrosion resistance of the magnesia carbon bricks.
